If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 90 = 2(7x + 1) + -3x Reorder the terms: 90 = 2(1 + 7x) + -3x 90 = (1 * 2 + 7x * 2) + -3x 90 = (2 + 14x) + -3x Combine like terms: 14x + -3x = 11x 90 = 2 + 11x Solving 90 = 2 + 11x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-11x' to each side of the equation. 90 + -11x = 2 + 11x + -11x Combine like terms: 11x + -11x = 0 90 + -11x = 2 + 0 90 + -11x = 2 Add '-90' to each side of the equation. 90 + -90 + -11x = 2 + -90 Combine like terms: 90 + -90 = 0 0 + -11x = 2 + -90 -11x = 2 + -90 Combine like terms: 2 + -90 = -88 -11x = -88 Divide each side by '-11'. x = 8 Simplifying x = 8
| 2x+12-x=14 | | 3(2x+9)=-18+33 | | -(4-x)=3/4(x+7) | | 10x-5=-8x+13 | | 304=-8(-6x+4) | | 6-(2x-8)=4-3x | | 14-3x=x+2 | | 14=7x-2x+9 | | x+x-150=180 | | -16+-10x=7x+18 | | 7-(4x-2)=8-5x | | 5+x-5x=-11 | | x+x/5=180 | | 15x+5x=6x | | 9(w-4)=8(7+w) | | 5.25Z-2.01=-8.94 | | 22+65=4+25 | | -34+3x=14-3x | | -8(x-8)-5=59 | | 8=-3x+2 | | 7(x-3)=7+6x | | 2x-6-3x=2 | | 15-.75g=13-50g | | e^3x+1=20 | | x-.10x=18.00 | | -3x+x^3=0 | | 76=(2x-6)3 | | 14+2p=20+15 | | 5x-9=6x-2 | | 7(y+2)=7y+14 | | 17=(-x-4)2 | | 9+9x=41-x |